2020
DOI: 10.3390/nu12020467
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal TG3- and TG2-Specific Plasma Cell Responses in Dermatitis Herpetiformis Patients Undergoing a Gluten Challenge

Abstract: Dermatitis herpetiformis (DH), a cutaneous manifestation of coeliac disease, is characterized by transglutaminase (TG) 3-targeted dermal immunoglobulin A (IgA) deposits. The treatment for DH is the same as for coeliac disease, namely a life-long gluten-free diet. DH patients typically have gluten-dependent circulating autoantibodies targeting TG3 and TG2, and plasma cells secreting such autoantibodies have been detected in the small intestinal mucosa. This study investigates the gluten-responsiveness of intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…DH patients were recently shown to have TG3-antibody secreting plasma cells at the level of the gut. Importantly, a gluten challenge of such patients revealed that gluten exposure drove rapid expansion of the TG3-specific plasma cell population in the lamina propria, and their frequency correlated with the serum titer of the corresponding autoantibodies [ 17 ]. Furthermore, there was no evidence that this cell population recognizes TG isozymes other than TG3 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DH patients were recently shown to have TG3-antibody secreting plasma cells at the level of the gut. Importantly, a gluten challenge of such patients revealed that gluten exposure drove rapid expansion of the TG3-specific plasma cell population in the lamina propria, and their frequency correlated with the serum titer of the corresponding autoantibodies [ 17 ]. Furthermore, there was no evidence that this cell population recognizes TG isozymes other than TG3 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a gluten challenge of such patients revealed that gluten exposure drove rapid expansion of the TG3-specific plasma cell population in the lamina propria, and their frequency correlated with the serum titer of the corresponding autoantibodies [ 17 ]. Furthermore, there was no evidence that this cell population recognizes TG isozymes other than TG3 [ 17 ]. This is in keeping with the results from the analysis of patient-derived immunoglobulins, indicating that cross-reacting antibodies are rare [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the first studies on the occurrence of TG3 autoantibody producing cells in DH were published. Ex vivo cultures of duodenal biopsies as well as intestinal plasma cell stainings performed on DH patient tissue strongly suggest that TG3-antibody producing cells are present at least in the small intestine ( 14 , 34 ). These cells seem to be highly DH-specific: despite the occasional occurrence of circulating TG3 antibodies, TG3 antibody producing plasma cells have only rarely been detected in CeD patients ( 14 , 34 ).…”
Section: B Cell Responses In Dhmentioning
confidence: 94%
“…Ex vivo cultures of duodenal biopsies as well as intestinal plasma cell stainings performed on DH patient tissue strongly suggest that TG3-antibody producing cells are present at least in the small intestine ( 14 , 34 ). These cells seem to be highly DH-specific: despite the occasional occurrence of circulating TG3 antibodies, TG3 antibody producing plasma cells have only rarely been detected in CeD patients ( 14 , 34 ). Furthermore, the TG3-specific plasma cells appear to be gluten-responsive as their frequency is increased during gluten challenge ( 14 ).…”
Section: B Cell Responses In Dhmentioning
confidence: 94%
See 1 more Smart Citation